1971
DOI: 10.2134/agronj1971.00021962006300030016x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Element Accumulation by Populations of Corn (Zea mays L.) Selected for High and Low Accumulation of P1

Abstract: The objective of the investigation of which this report is a part was to identify chemical elements, organic compounds, or metabolic processes which are associated with genetically controlled P accumulation in corn (Zea mays L.). Two populations of corn, each with subpopulations selected for high and low P in ear leaves, were produced by randomly sib mating the F2 and five and six subsequent generations of an early maturing single‐crossed hybrid and a late maturing single‐cross hybrid. Each single‐cross hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Hybrids resulted from crossing of low P-accumulation inbred lines were also low accumulators, and those resulted from crossing of high P-accumulation inbred lines, were high accumulators. Baker et al (1970Baker et al ( ,1971 found differences among hybrids for the leaf P-accumulation and grain yield and confirmed the high heritability for this character. The leaf P accumulation was not correlated with plant ability in Puptake, but was associated to physiological processes independent of roots.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Hybrids resulted from crossing of low P-accumulation inbred lines were also low accumulators, and those resulted from crossing of high P-accumulation inbred lines, were high accumulators. Baker et al (1970Baker et al ( ,1971 found differences among hybrids for the leaf P-accumulation and grain yield and confirmed the high heritability for this character. The leaf P accumulation was not correlated with plant ability in Puptake, but was associated to physiological processes independent of roots.…”
Section: Resultssupporting
confidence: 54%
“…These variables together with shoot and total DM explained most of the variability within soybean germplasm for the P-efficiency characters (Figure 1). Other researchers have reported low nutrient concentration or accumulation in the plant tissue as a nutrient efficiency character (Barber et al, 1967;Baker et al, 1970;1971;Spehar & Souza, 1999). Barber et al (1967) observed genetic controlled variations in P-accumulation in maize.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In lucerne (Hill and Lanyon, 1983) and maize (Baker et al, 1971), selection for increases and decreases in %P level of shoots has been achieved with realised heritabilities for lucerne of 0.17 to 0.36 (Miller et al, 1987). Similarly in lucerne selections for high and low %N levels have been successful (Teuber et al, 1984).…”
Section: Heritability Of N and P Contentmentioning
confidence: 99%
“…Neikova-Bocheva et al (15) emphasized the importance of chromosomal and cytoplasmic effects on the uptake and accumulation of elements in plants. The uptake and accumulation of phosphorus by maize has been studied extensively by Gorsline et al (10), Baker et al (1), Thomas and Baker (19), Clark et al (6), and 502 RAKHAETAL.…”
Section: Introductionmentioning
confidence: 99%